Penilaian Kapabilitas Penerapan Manajemen Risiko Teknologi Informasi Menggunakan Kerangka Kerja COBIT 5 (Studi pada PDAM Kota Malang Jawa Timur) - Yani Iriana Putri; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PDAM Kota Malang's target it utilizing an effective information technology. Therefore the company has priority on improving reability of information system management, service system improvements, customer data management, development and implementation of the applications. In order to measure the implementation of risk management, an assessment had been done to capability level of EDM03 subdomain (ensure risk optimization), APO12 (manage risk) and APO13 (manage security) using COBIT 5 Framework. This research used self assessment. Started from choosing processes to asses, assessment for level 1, assessment for level 2 to 5, recording all of the assessment result, gap analyzing, and making recommendations. The result of capability level were obtained through several methods, viz. interviews, observation, and self-assessment worksheet. Recommendations were expected to assist the company in archiving the targeted level in EDM03, APO12, and APO13 processes. Where this three processes were in capability level 1 and the targeted level is in level 2. Thus, the gap of the three subdomain is 1. Recommendations for the company are related to documents of each processes which needed to be improved, suggestion to do a further analysis to know the possibility that will occur in the future, establishing a special team for risk and security management, separation of duties and responsibilities, and determining methods to control each processes.